Current trends in ultramarathon running - Spittler, J.; Oberle, L. (Current Sports Medicine Reports, 2019)
Exercise is universally recognized for its health benefits and distance running has long been a popular form of exercise and sport. Ultramarathons, defined as races longer than a marathon, have become increasingly popular in recent years. The diverse ultramarathon distances and courses provide additional challenges in race performance and medical coverage for these events. As the sport grows in popularity, more literature has become available regarding ultramarathon-specific illnesses and injuries, nutrition guidelines, psychology, physiologic changes, and equipment. This review focuses on recent findings and trends in ultramarathon running.